2012
DOI: 10.1097/jcp.0b013e31825368b7
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Central Serotonin Affects Emotional Information Processing in Impulsive Aggressive Personality Disorder

Abstract: Individuals with clinically relevant levels of impulsive aggression may be susceptible to effects of serotonergic depletion on emotional information processing, showing a tendency to exaggerate their impression of the intensity of angry expressions and to report an angry mood state after tryptophan depletion. This may reflect heightened sensitivity to the effects of serotonergic dysregulation, and suggests that what underlies impulsive aggression is either supersensitivity to serotonergic disturbances or susce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…In a laboratory aggression paradigm, tryptophan depletion was associated with reduced insula activity during selection of severity of aggressive response 89 . Acute challenges to the serotonergic system have also been shown to influence the processing of emotional faces 96 and associated neural activity. Tryptophan depletion modulated the functional connectivity that occurs between the amygdala and prefrontal regions specifically while processing angry faces, as opposed to neutral or sad faces 59 …”
Section: Neurochemistry and Pharmacology: Serotoninmentioning
confidence: 99%
“…In a laboratory aggression paradigm, tryptophan depletion was associated with reduced insula activity during selection of severity of aggressive response 89 . Acute challenges to the serotonergic system have also been shown to influence the processing of emotional faces 96 and associated neural activity. Tryptophan depletion modulated the functional connectivity that occurs between the amygdala and prefrontal regions specifically while processing angry faces, as opposed to neutral or sad faces 59 …”
Section: Neurochemistry and Pharmacology: Serotoninmentioning
confidence: 99%
“…The main neurotransmitter implicated in the aggressive behavior of Maoa KO mice is 5-HT. The bulk of evidence has shown that impulsive aggression is consequent to a reduction of 5-HT content; for example, dietary restriction of the 5-HT precursor tryptophan impairs emotional processing and increases the susceptibility for outbursts in aggressive patients (Lee et al, 2012; Passamonti et al, 2012; Grady et al, 2013). As noted above, however, Maoa KO mice exhibit pronounced elevations of synaptic 5-HT levels; this apparent conundrum may be explained by the multifaceted contributions of 5-HT to the ontogeny of aggression across multiple developmental stages and different brain regions.…”
Section: Neurochemical Bases Of the Link Between Maoa And Aggressionmentioning
confidence: 99%
“…For instance, a negative correlation between an indicator for 5-HT transporter binding and aggression was found in personality disorder patients with IED (Coccaro et al, 2010;Coccaro, 2012) and IED patients show reduced 5-HT transporter availability in the anterior cingulate cortex (Frankle et al, 2005). Moreover, males with IED tend to increase intensity ratings of angry faces after tryptophan depletion that reduces 5-HT availability (Lee et al, 2012). Conversely, fluoxetine (a selective serotonin reuptake inhibitor (SSRI) that increases 5-HT availability) was shown to reduce impulsive aggressive behavior in patients with personality disorders and comorbid IED (Coccaro et al, 2009).…”
Section: Introductionmentioning
confidence: 99%